Heterogeneous electromagnetic wave absorption composite nanofiber and preparation method thereof
By a composite nanofiber material embedded in COS2 nanoparticles in carbon nanoplasts, the efficient electromagnetic wave absorption of high -efficiency electromagnetic waves within the wide frequency range was used to solve the limitations of traditional materials on the impedance matching and loss path. Electromagnetic interference shielding and information security protection.
Patent Information
- Application Number
- CN202411507051.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
Smart Images

Figure CN119352196A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorption, and in particular relates to a non-homogeneous electromagnetic wave absorbing composite nanofiber and a preparation method thereof. Background Art
[0002] With the rapid popularization of modern electronic devices, the increase in electromagnetic wave radiation not only interferes with the normal operation of electronic devices, but also poses a potential threat to human health and information security. Therefore, the research and development of materials that can effectively absorb electromagnetic waves has become an important research direction in the current field of materials science and electromagnetic compatibility. Such materials not only need to have the characteristics of light weight, thin layer, wide bandwidth and strong absorption, but also need to achieve effective electromagnetic wave attenuation without increasing the load on the equipment.
[0003] Carbon-based materials have attracted extensive attention in the field of electromagnetic wave absorption due to their excellent electrical conductivity, low density and diverse morphologies. They also have good chemical flexibility and can further optimize material properties through different doping or compounding methods. However, traditional carbon fiber absorbers have certain limitations in loss path and impedance matching, making it difficult to meet the demand for more efficient absorbers. Summary of the invention
[0004] To solve the above problems, the present invention provides a heterogeneous electromagnetic wave absorbing composite nanofiber, comprising a matrix composed of carbon nanofibers and CoS2 nanoparticles dispersed on the surface or inside of the carbon nanofibers in an embedded form.
[0005] In the present invention, the synergistic effect of carbon nanofibers and CoS2 nanoparticles achieves efficient electromagnetic wave absorption, which includes the following mechanisms: (1) Conductive loss mechanism: Carbon nanofibers, as a conductive skeleton, promote the migration and conduction of carriers by improving the conductivity of the material. The interface between CoS2 nanoparticles and carbon fibers helps to form local currents, resulting in the dissipation of electric field energy. This conductive loss mainly comes from the migration of free electrons, which move and dissipate electrical energy under the action of electromagnetic waves, thereby enhancing the attenuation ability of electromagnetic waves; (2) Polarization loss mechanism: The introduction of CoS2 nanoparticles significantly enhances the polarization loss effect of the composite material. CoS2 in the material has a strong dipole polarization ability, and the doping of heteroatoms (such as nitrogen, sulfur, and oxygen) in the carbon fiber further promotes defect polarization and interface polarization. Under the action of the alternating electric field of the electromagnetic wave, these polarization processes lag behind the electric field changes, resulting in polarization losses, thereby enhancing the absorption of electromagnetic waves; (3) CoS2 nanoparticles are embedded in the surface and interior of the carbon fiber, forming a complex three-dimensional structure. This structure can increase the multiple scattering and reflection paths of electromagnetic waves inside the material, thereby extending the propagation time of electromagnetic waves in the material and increasing its loss. A strong interface scattering effect is also produced at the interface between the nanoparticles and the fibers, further improving the absorption performance; (4) The impedance matching performance of the material is an important factor affecting the absorption effect. By adjusting the ratio of CoS2 to carbon fiber and the structure of the composite material, the input impedance of the composite material can be close to the impedance of free space, achieving good impedance matching. The optimization of impedance matching ensures that more electromagnetic waves can enter the material and be effectively absorbed; (5) The interface between the non-uniformly distributed CoS2 nanoparticles and carbon-based materials may produce different electromagnetic wave absorption and attenuation effects. The local aggregation and void structure of the nanoparticles can enhance the multiple scattering effect and interface polarization loss, thereby improving the absorption performance of electromagnetic waves. Through these synergistic effects, the CoS2 / C composite nanofiber material can effectively absorb electromagnetic waves and show excellent electromagnetic wave absorption performance, especially in a wide frequency range and under small thickness conditions to achieve efficient absorption.
[0006] Furthermore, the diameter of the composite nanofibers is 300 nanometers, and the particle size of the CoS2 nanoparticles is 80-100 nanometers.
[0007] On the other hand, the present invention provides a method for preparing inhomogeneous electromagnetic wave absorbing composite nanofibers, comprising the following steps: Step 1, weigh 0.5 g of polyacrylonitrile and dissolve it in 5 ml of N,N-dimethylformamide, and stir at 60°C for 2 hours until it is evenly dissolved; Step 2, add 2.5 mmol of cobalt acetate and continue stirring at room temperature overnight to obtain a uniform purple solution; Step 3, the prepared solution was loaded into a 5 ml syringe with a stainless steel needle for electrospinning; Step 4, drying the polyacrylonitrile / Co composite membrane obtained after electrospinning; Step 5, placing the dried polyacrylonitrile / Co composite film in a tubular furnace, heating it under a nitrogen atmosphere, and keeping it warm for 2 hours to carbonize it, thereby obtaining carbon nanofibers containing metallic cobalt; Step 6: Place thiourea and carbonized nanofibers in different areas of a tubular furnace, heat them in a nitrogen atmosphere, and keep them warm for 30 minutes to perform a sulfurization reaction to convert cobalt into CoS2, thereby obtaining CoS2 / C composite nanofibers.
[0008] Furthermore, in step 3, the stainless steel needle is a 21-gauge steel needle.
[0009] Furthermore, in step 3, during electrospinning, the receiving distance was 18 cm, the voltage was 18 kV, the flow rate was 1.3 ml / h, the ambient temperature was 20°C, and the humidity was 40%.
[0010] Furthermore, in step 4, the drying temperature is 60° C. and the drying time is 2 hours.
[0011] Furthermore, in step 5, the heating rate is 1°C / min.
[0012] Furthermore, in step 5, heating is performed to 800°C.
[0013] Furthermore, in step 6, the heating rate is 1°C / min. Furthermore, in step 6, heating is performed to 450°C.
[0014] Beneficial effects of the present invention: (1) The composite nanofibers of the present invention exhibit excellent electromagnetic wave absorption performance in a wide frequency range, with a minimum reflection loss of -59.84 dB and an effective absorption bandwidth of 4.9 GHz, especially in the X-band (8-12 GHz). This makes the material suitable for electromagnetic wave interference suppression and information security protection of electronic equipment.
[0015] (2) The composite material is only 2.5 mm thick and still maintains high absorption performance at a relatively low thickness, meeting the current demand for lightweight, thin-layer electromagnetic wave absorbing materials. It can effectively reduce the burden on equipment and is suitable for occasions that require lightweight design.
[0016] (3) By adjusting the ratio of CoS2 to carbon fiber and the structure of the composite material, the present invention achieves excellent impedance matching characteristics, allowing more electromagnetic waves to enter the material and be effectively absorbed, avoiding reflection problems and further improving the absorption efficiency.
[0017] (4) CoS2 nanoparticles are distributed on the surface or inside of carbon fibers to form a three-dimensional porous network structure, which can effectively increase the multiple scattering paths of electromagnetic waves inside the material, prolong the propagation time of electromagnetic waves, and thus enhance the absorption and attenuation of electromagnetic waves.
[0018] (5) The material is prepared by electrospinning and high-temperature treatment process, which is simple and scalable, easy to achieve large-scale production, and has high potential for industrial application.
[0019] Based on the above beneficial effects, the present invention has good application prospects in the field of electromagnetic wave absorption technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 . (a) Schematic diagram of the synthesis process of CoS2 / C composite nanofibers; (bf) Scanning electron microscopy (SEM) images of PAN-based nanofibers at different cobalt salt concentrations: 1.5 mmol (b, f), 2 mmol (c, g), 2.5 mmol(d, h), 3 mmol (e, i); (jq) SEM images of composite nanofibers after sulfurization treatment: CoS2 / C-1 (j,n), CoS2 / C-2 (k, o), CoS2 / C-3 (l, p), CoS2 / C-4 (m, q).
[0021] Figure 2 . (a) X-ray diffraction (XRD) pattern of CoS2 / C composite nanofibers; (be) X-ray photoelectron spectroscopy (XPS) high-resolution spectrum of CoS2 / C-3 composite materials: (b) full spectrum, (c) C 1s spectrum, (d) Co 2p spectrum, (e) S 2p spectrum; (f) Raman spectrum of CoS2 / C composite nanofibers; (g) SEM magnified image, (h) transmission electron microscopy (TEM) image, (i) high-resolution transmission electron microscopy (HRTEM) image, (j) selected area electron diffraction (SAED) image, (kn) element distribution map of CoS2 / C-3 composite nanofibers.
[0022] Figure 3. Three-dimensional reflection loss diagrams and vertical views of CoS2 / C composite nanofibers: (a1, a2) CoS2 / C-1, (b1, b2) CoS2 / C-2, (c1, c2) CoS2 / C-3, (d1, d2) CoS2 / C-4.
[0023] Figure 4 . Electromagnetic parameters of CoS2 / C composite nanofibers: (a) real part of relative complex permittivity, (b) imaginary part of relative complex permittivity, (c) dielectric loss tangent, (d) real part of relative complex magnetic permeability, (e) imaginary part of relative complex magnetic permeability, (f) magnetic loss tangent.
[0024] Figure 5 . (a) Theoretical model of CoS2 / C-3; (b) Charge density difference diagram: the red area indicates the increase of electrons, and the blue area indicates the decrease of electrons, indicating that electrons flow from CoS2 to the carbon skeleton; (c) Theoretical simulation dielectric constants of CoS2 and CoS2 / C-3; (d) Reflection spectrum; (e) Loss function.
[0025] Figure 6 . Schematic diagram of the wave absorption mechanism of CoS2 / C composite nanofibers.
[0026] Figure 7 . (a) Simulation model of radar cross section (RCS); (b) CST simulation results of perfect electric conductor (PEC); (c) CST simulation results of PEC covering CoS2 / C-2; (d) CST simulation results of PEC covering CoS2 / C-3; (e) RCS values of samples at different incident angles; (f) RCS attenuation values of CoS2 / C-2 and CoS2 / C-3. DETAILED DESCRIPTION
[0027] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples.
[0028] The present invention provides a method for preparing inhomogeneous electromagnetic wave absorbing composite nanofibers, comprising the following steps: Step 1: Weigh 0.5 g of polyacrylonitrile (PAN) and dissolve it in 5 ml of N,N-dimethylformamide (DMF), and stir at 60°C for 2 hours until it is uniformly dissolved.
[0029] Step 2: Add 2.5 mmol of cobalt acetate (Co(CH3COO2·4H2O)) and continue stirring at room temperature overnight to obtain a uniform purple solution.
[0030] Step 3: Load the prepared solution into a 5 ml syringe and use a No. 21 stainless steel needle for electrospinning. During electrospinning, the receiving distance is 18 cm, the voltage is 18 kV, the flow rate is 1.3 ml / h, the ambient temperature is 20°C, and the humidity is 40%.
[0031] Step 4: Dry the polyacrylonitrile / Co composite membrane obtained after electrospinning at 60° C. for 2 hours.
[0032] Step 5: Place the dried polyacrylonitrile / Co composite film in a tubular furnace, heat it to 800° C. at a heating rate of 1° C. / min in a nitrogen atmosphere, and keep it at this temperature for 2 hours to carbonize it, thereby obtaining carbon nanofibers containing metallic cobalt.
[0033] Step 6: Place thiourea and carbonized nanofibers in different areas of a tubular furnace, heat to 450°C at a rate of 1°C / min in a nitrogen atmosphere, and keep warm for 30 minutes to perform a sulfidation reaction to convert cobalt into CoS2, thereby obtaining CoS2 / C composite nanofibers.
[0034] Figure 1 (a) The preparation process of composite nanofibers is given. First, polyacrylonitrile (PAN)-based nanofiber membranes are prepared by electrospinning technology, followed by carbonization in a nitrogen atmosphere to convert PAN into carbon fibers and convert the cobalt in it into metallic cobalt (Co). Finally, by sulfurization, the metallic cobalt is converted into cobalt disulfide (CoS2), thereby forming CoS2 / carbon composite nanofibers in a carbon fiber matrix. Figure 1 (bf) shows the surface morphology of PAN-based nanofibers prepared at different cobalt salt concentrations (1.5 mmol, 2 mmol, 2.5 mmol, 3 mmol), which correspond to the obtained samples CoS2 / C-1, CoS2 / C-2, CoS2 / C-3, and CoS2 / C-4. The fiber surface is flat and the diameter is about 350 nm. The addition of cobalt salt has little effect on the fiber size. Figure 1 (jq) shows the surface morphology of CoS2 / carbon composite nanofibers after carbonization and sulfurization. After carbonization, the fiber diameter is reduced to about 300 nm, and CoS2 nanoparticles with a diameter of 80-100 nm are embedded on the fiber surface to form a three-dimensional network structure, which helps to enhance the conductivity and microwave absorption properties of the material.
[0035] Figure 2(a) shows the crystal structure of CoS2 / carbon composite nanofibers. The diffraction peaks in the figure are located at 27.8°, 32.3°, 36.2°, 39.8°, 46.3° and 54.9°, corresponding to the (111), (200), (210), (211), (220) and (311) crystal planes of CoS2, respectively. These peaks indicate that the cobalt salt has been successfully converted into cobalt disulfide (CoS2) and that the fiber matrix is composed of carbon. Figure 2 (be) is to analyze the chemical bonding state of elements on the surface of the composite material. Figure 2 (b) The presence of S, Co, N, C, and O elements in the sample was confirmed. Figure 2 (c) is the C 1s spectrum, showing chemical bonds such as CC / C=C, CN and C=O. Figure 2 (d) is the Co 2p spectrum, indicating that Co exists in CoS2 and has Co 2+ and Co 3+ chemical state. Figure 2 (e) is the S 2p spectrum, showing the presence of metal-sulfur bonds and sulfur oxides, further proving the formation of CoS2. Figure 2 (f) is a Raman spectrum showing the degree of graphitization of carbon-based fibers. The intensity ratio of the D band and the G band (I D / I G ) is about 1.1, indicating that the carbon fiber has a high graphitization level and good conductivity. Figure 2 (g) is a magnified SEM image showing the CoS2 nanoparticles embedded in the fiber surface. Figure 2 (h) is a TEM image, which further demonstrates the nanostructure of the fiber surface. Figure 2 (i) is a high-resolution TEM (HRTEM) image showing the crystal structure of CoS2, with a lattice spacing of 0.277 nm, corresponding to the (200) crystal plane of CoS2. Figure 2 (j) is a selected area electron diffraction (SAED) image, which confirms the crystal structure of CoS2. Its diffraction rings correspond to the (200), (220), (410) and (422) crystal planes of CoS2, respectively. Figure 2 (kn) are element distribution maps. These element maps show the uniform distribution of Co and S elements in the CoS2 / carbon composite nanofibers, further confirming that the CoS2 nanoparticles are uniformly embedded in the carbon fiber matrix.
[0036] Figure 3 (a1-a2) is the reflection loss diagram of CoS2 / C-1 sample, which shows the electromagnetic wave absorption effect at different thicknesses. The minimum reflection loss (RL min ) is -16.16 dB, the thickness is 4.5 mm, and the absorption effect is poor. Figure 3(b1-b2) is the reflection loss diagram of CoS2 / C-2 sample: This sample shows better absorption performance, RL min It is -35.92 dB and the thickness is 3.5 mm, indicating that it has a certain ability to absorb electromagnetic waves. Figure 3 (c1-c2) is the reflection loss diagram of CoS2 / C-3 sample. The sample shows the best absorption performance at 11.1 GHz, RL min It reaches -59.84 dB with a thickness of 2.5 mm. In addition, the effective absorption bandwidth of the CoS2 / C-3 sample almost covers the entire X-band, showing good application potential. Figure 3 (d1-d2) is the reflection loss diagram of CoS2 / C-4 sample. The RL min The reflection loss of the CoS2 / C-3 sample is -27.06 dB, and the thickness is 4.5 mm. The absorption performance is similar to that of CoS2 / C-1, which is relatively general. It can be seen from these reflection loss graphs that with the increase of CoS2 content, the electromagnetic wave absorption performance of the material gradually improves. In particular, the CoS2 / C-3 sample exhibits the best absorption performance, which is due to the good impedance matching and strong attenuation ability of the material. The improvement in absorption performance is attributed to the synergistic effect between CoS2 nanoparticles and carbon fibers. The embedding of CoS2 increases the dielectric constant of the composite material, enabling it to better store electromagnetic energy. At the same time, the interface polarization and multiple scattering effects between the nanoparticles and carbon fibers enhance the attenuation ability of the material. In addition, the embedding of CoS2 particles also enhances the conductive loss and polarization loss of the composite material, so that the electromagnetic waves are effectively dissipated inside the material, thereby improving the absorption performance.
[0037] Figure 4 (ab) are the real part (ε') and imaginary part (ε'') of the relative complex dielectric constant of the composite nanofibers. The real part ε' reflects the material's ability to store electromagnetic energy, while the imaginary part ε'' reflects the material's ability to lose electromagnetic energy. As the CoS2 content increases, the ε' value of the composite material increases, indicating that its ability to store electromagnetic energy is enhanced. This is because the embedding of CoS2 particles in the carbon fiber matrix increases the dielectric constant of the material and enhances the material's response to electromagnetic energy. The decrease in the ε'' value indicates that the material's energy loss capacity has weakened, which may be due to the excessively high CoS2 content, resulting in partial reflection of electromagnetic waves instead of complete absorption. Figure 4 (c) is the dielectric loss tangent (tanδ) of the composite nanofibers E ). The dielectric loss tangent reflects the electromagnetic energy dissipation capacity of the material. With the increase of CoS2 content, the dielectric loss tangent tanδ EThe trend of is similar to that of the imaginary part ε'', indicating that the embedding of CoS2 nanoparticles enhances polarization loss and conductive loss. The conductive loss mainly comes from the migration of free electrons and the local current formed at the interface between carbon fiber and CoS2. The polarization loss comes from various effects such as interface polarization, defect polarization and dipole polarization of nanoparticles. Figure 4 (de) is the real part (μ') and imaginary part (μ'') of the relative complex magnetic permeability of the composite nanofibers. The μ' values of all samples are close to 1, and the μ'' values are close to 0, indicating that the material has basically no magnetic properties, and the absorption of electromagnetic waves mainly depends on dielectric loss rather than magnetic loss. Figure 4 (f) is the magnetic loss tangent (tanδ) of the composite nanofibers M ): The value of the magnetic loss tangent is close to 0, indicating that the magnetic loss contributes very little to the electromagnetic wave absorption of the composite material, and the loss of electromagnetic waves mainly depends on the dielectric loss. By analyzing the dielectric constant and the dielectric loss tangent, it can be concluded that the electromagnetic wave absorption performance of the composite material mainly depends on the dielectric loss, especially the polarization loss and the conductive loss. The embedding of CoS2 nanoparticles significantly enhances the polarization ability of the material, so that the electric dipole lags behind the electric field change under the alternating electric field, thereby generating polarization loss. At the same time, the free electrons in the carbon fiber dissipate electromagnetic energy through local currents, further enhancing the conductive loss. In addition, the relatively low magnetic permeability and magnetic loss tangent indicate that the electromagnetic wave absorption mechanism of this type of material does not rely on magnetic materials, but achieves the wave absorption effect by regulating the dielectric properties.
[0038] Figure 5 (a) is the theoretical model of CoS2 / C composite nanofibers, where CoS2 nanoparticles are embedded in the carbon fiber matrix to form a heterojunction interface. This structure promotes the flow of charge between CoS2 and carbon fiber through electron transfer and hybridization effects, thereby enhancing the loss of electromagnetic waves. Figure 5 (b) is a charge density difference diagram, in which the red area indicates an increase in electron density and the blue area indicates a decrease in electron density. It can be seen that electrons are transferred from CoS2 to carbon fibers, indicating that significant charge transfer occurs between CoS2 and carbon fibers, resulting in orbital hybridization of electrons. This electron transfer and hybridization effect strengthens the interfacial interaction between CoS2 and carbon fibers, increasing the conductivity and polarization loss of the composite material. Figure 5 (c) is the dielectric constant of theoretical simulation. The calculation results of static dielectric constant show that the dielectric constants of CoS2 and CoS2 / C composite materials are 37.97 and 56.73, respectively. With the increase of energy, the real dielectric constant of CoS2 / C is always higher than that of CoS2, and it shows a higher polarization response in the low energy region. This shows that the CoS2 / C composite material has a stronger polarization ability, which helps to improve the electromagnetic wave absorption performance of the material. Figure 5(d) is the reflectivity of the composite nanofibers. The calculation results of the reflectivity show that the reflectivity of the CoS2 / C composite material is lower than that of pure CoS2 in the entire energy range, especially in the low energy region, where CoS2 / C shows a significantly reduced reflectivity. This means that the composite material can more effectively reduce the reflection of electromagnetic waves, thereby enhancing absorption. Figure 5 (e) is the loss function, and the energy loss of CoS2 and CoS2 / C is concentrated in the range of 10-25 eV. Although CoS2 shows a higher loss peak, the loss range of CoS2 / C composite is wider, indicating that the composite can effectively absorb electromagnetic waves in a wider frequency range. Theoretical calculations show that the electromagnetic wave absorption performance of CoS2 / C composite is better than that of pure CoS2, which is mainly attributed to the transfer of electrons from CoS2 to carbon fiber. This charge transfer enhances the interface polarization and conductive loss. The significant increase in the dielectric constant indicates that the composite has a stronger polarization ability, and the reduction in reflectivity means that the material can reduce reflection loss, allowing more electromagnetic waves to enter the material and be absorbed. The calculation of the loss function further shows that the CoS2 / C composite has excellent electromagnetic wave absorption ability in a wider frequency range and is suitable for a wide range of electromagnetic interference protection applications.
[0039] Figure 6 Schematic diagram of the wave absorption mechanism. Figure 6 The three-dimensional porous network structure formed by CoS2 / C composite nanofibers is demonstrated. The interweaving between fibers and the embedding of CoS2 nanoparticles cause multiple scattering and reflection of electromagnetic waves inside the material. This multiple scattering effect prolongs the propagation path of electromagnetic waves inside the material, increases the interaction between electromagnetic waves and materials, and thus improves the loss capacity of electromagnetic waves. The combination of CoS2 and carbon fibers greatly improves the conductivity of the composite material. In the composite material, free electrons migrate in the carbon fibers, resulting in conductive losses. The embedding of CoS2 nanoparticles provides additional conductive paths, further enhancing the conductive losses of the material. The increase in conductive losses causes the energy of electromagnetic waves to be dissipated more inside the material, thereby reducing the reflection of electromagnetic waves and improving the absorption effect. A heterojunction is formed at the interface between CoS2 nanoparticles and carbon fibers. Under the action of electromagnetic waves, charges accumulate at the interface, resulting in interface polarization. The interface polarization effect lags behind the change in the electric field when the frequency of the electromagnetic wave changes, resulting in energy loss of the electromagnetic wave. Interface polarization is one of the main polarization loss mechanisms in composite materials and makes an important contribution to improving the electromagnetic wave absorption performance. Heteroatom doping (such as nitrogen, sulfur, and oxygen) introduces a defect polarization mechanism. These defects form dipoles under the action of electromagnetic waves, and lag as the frequency of the electromagnetic waves changes, resulting in polarization losses. At the same time, the dipole polarization effect of CoS2 itself also has a positive effect on electromagnetic wave absorption. Through these polarization effects, the energy of electromagnetic waves is converted into heat energy and thus effectively absorbed. Figure 6The synergistic effect between CoS2 and carbon fiber was also demonstrated. The combination of CoS2 particles and carbon fiber not only enhances the conductive loss and polarization loss, but also produces more complex multiple scattering and interface polarization effects in the composite material. This synergistic effect is the key to the composite material's ability to achieve excellent electromagnetic wave absorption performance over a wide frequency range.
[0040] Figure 7 (a) shows the simulation model for radar cross section (RCS) testing. The model consists of a perfect electric conductor (PEC) covered with CoS2 / C composite nanofiber materials of different thicknesses. The size of the model is 180 mm², the electromagnetic wave is incident along the Z-axis (from positive to negative), and the electric field polarization direction is along the X-axis. Open boundary conditions are applied in all directions to simulate the propagation and scattering of electromagnetic waves in free space. Figure 7 (bd) are the three-dimensional simulation results of radar wave scattering signals: Figure 7 (b) shows the strong scattering signal of a perfect electric conductor (PEC) under radar wave irradiation. As an ideal reflector, PEC hardly absorbs electromagnetic waves, resulting in the strongest scattering signal. Figure 7 (c) shows the scattering signal when PEC covers the CoS2 / C-2 composite material. The scattering signal is significantly weakened, indicating that the CoS2 / C-2 material has a certain wave absorbing ability. Figure 7 (d) shows the scattering signal when PEC covers the CoS2 / C-3 composite material, and the scattering is further weakened, indicating that the CoS2 / C-3 material has the best electromagnetic wave absorption effect. Figure 7 (e) is the RCS value of the sample at different incident angles. At different incident angles, the RCS value is used to evaluate the wave absorption effect of the material. The RCS value of the CoS2 / C-3 composite material is significantly lower than that of PEC and CoS2 / C-2 in the incident angle range of -90° to 90°, indicating that it has good wave absorption performance at multiple angles and can effectively reduce the reflection and scattering of radar waves. Figure 7(f) is the RCS attenuation value. The RCS attenuation value indicates the reduction in the radar cross section of the material compared to PEC. The figure shows that all samples covered with CoS2 / C composites can effectively reduce the RCS value, indicating that these materials can reduce the scattering intensity of radar signals. Among them, the RCS attenuation of the CoS2 / C-3 composite is the most significant, indicating that it has the greatest advantage in wave absorption performance. Radar cross section testing is a key indicator to measure the ability of a material to absorb and scatter electromagnetic waves. CoS2 / C composites, especially CoS2 / C-3, can effectively reduce the reflection of electromagnetic waves and improve absorption capacity through their three-dimensional network structure and embedded CoS2 nanoparticles. The synergistic effect of CoS2 nanoparticles and carbon fibers enhances the polarization loss and conductive loss of the composite material, thereby reducing the scattering of electromagnetic waves under the irradiation of radar waves. The good impedance matching performance of the composite material allows more electromagnetic waves to enter the material instead of being reflected, thereby further improving the absorption efficiency of electromagnetic waves.
[0041] The CoS2 / carbon composite nanofiber material of the present invention exhibits excellent electromagnetic wave absorption performance, especially significant absorption effect in a wide frequency range. Due to its light weight, thin layer and high efficiency wave absorption characteristics, it can be widely used in the fields of electromagnetic interference shielding of electronic equipment, radar stealth technology and information security protection in the future. The preparation method of the composite material is simple, and large-scale production can be achieved by using mature technologies such as electrostatic spinning and high temperature treatment. This means that the material has good industrialization potential, can meet the market demand for high-efficiency wave absorbing materials, and promote its application in the fields of electronics, military and communications.
[0042] Preferably, in order to further improve the absorbing performance, the substrate surface is designed with micro-nano structures, such as nano-pillars or nano-pit structures, which helps to increase the scattering path of electromagnetic waves and further improve the overall efficiency of the absorbing material. Surface roughening can significantly enhance the interaction between electromagnetic waves and materials and improve the loss effect. Preferably, the material of the substrate is aluminum oxide. Aluminum oxide has excellent high temperature resistance and chemical corrosion resistance. Aluminum oxide substrate with a roughened surface can increase the scattering of electromagnetic waves and improve the absorbing effect. In addition, its good mechanical strength makes it suitable for high-intensity application scenarios, such as aerospace and electronic equipment.
[0043] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A non-homogeneous electromagnetic wave absorbing composite nanofiber, characterized in that: The invention comprises a matrix composed of carbon nanofibers and CoS2 nanoparticles dispersed on the surface or inside of the carbon nanofibers in an embedded form.
2. The inhomogeneous electromagnetic wave absorbing composite nanofiber according to claim 1, characterized in that: The diameter of the composite nanofiber is 300 nanometers, and the particle size of the CoS2 nanoparticles is 80-100 nanometers.
3. A method for preparing heterogeneous electromagnetic wave absorbing composite nanofibers, characterized in that: The steps include: Step 1, weigh 0.5 g of polyacrylonitrile and dissolve it in 5 ml of N,N-dimethylformamide, and stir at 60°C for 2 hours until it is evenly dissolved; Step 2, add 2.5 mmol of cobalt acetate and continue stirring at room temperature overnight to obtain a uniform purple solution; Step 3, the prepared solution was loaded into a 5 ml syringe with a stainless steel needle for electrospinning; Step 4, drying the polyacrylonitrile / Co composite membrane obtained after electrospinning; Step 5, placing the dried polyacrylonitrile / Co composite film in a tubular furnace, heating it under a nitrogen atmosphere, and keeping it warm for 2 hours to carbonize it, thereby obtaining carbon nanofibers containing metallic cobalt; Step 6: Place thiourea and carbonized nanofibers in different areas of a tubular furnace, heat them in a nitrogen atmosphere, and keep them warm for 30 minutes to perform a sulfurization reaction to convert cobalt into CoS2, thereby obtaining CoS2 / C composite nanofibers.
4. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 3, characterized in that: In step 3, the stainless steel needle is a No. 21 steel needle.
5. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 4, characterized in that: In step 3, during electrospinning, the receiving distance was 18 cm, the voltage was 18 kV, the flow rate was 1.3 ml / h, the ambient temperature was 20 °C, and the humidity was 40%.
6. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 5, characterized in that: In step 4, the drying temperature is 60° C. and the drying time is 2 hours.
7. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 6, characterized in that: In step 5, the temperature is increased at a rate of 1°C / min.
8. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 7, characterized in that: In step 5, heating is performed to 800°C.
9. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 8, characterized in that: In step 6, the temperature is increased at a rate of 1°C / min.
10. The method for preparing the heterogeneous electromagnetic wave absorbing composite nanofiber according to claim 9, characterized in that: In step 6, heating is performed to 450°C.
Citation Information
Cited By
Composite base material wave-absorbing hose and manufacturing method thereof
CN120583665A